A Real Witcher—Slavic or Universal; from a Book, a Game or a TV Series? In the Circle of Multimedia Adaptations of a Fantasy Series of Novels “The Witcher” by A. Sapkowski - Sławomir Gawroński; Kinga Bajorek (Arts, 2020)
A series of novels about a witcher, written by Andrzej Sapkowski almost thirty years ago, has now become an inspiration for the creation of mass productions of mainstream popular culture—film and multimedia adaptations for use in computer games. It is one of the few examples of global messages of mass culture being based on Polish creativity. The recognition of “The Witcher”, due to the Netflix production, soon contributed to building the national pride of Polish people, and at the same time sparked a discussion in Central and Eastern European countries on the consequences of the multimedia adaptation of Andrzej Sapkowski’s prose. Questions about the dissonance between the Slavic and universal dimensions of “The Witcher” in relation to the original novels and their adaptations are a part of the traditional discourse on the adaptability of literature and its consequences for the reception by the audience. This article tries to capture the specific character of the adaptations of Andrzej Sapkowski’s literature from the point of view of typology, known from the literature of the subject, as well as to answer the question about the consequences of the discrepancy between the original book and its adaptations in the form of a film, a TV series, and computer games. The considerations in the article were based on the literature analysis and the research based on the existing sources.